2005
DOI: 10.1111/j.1468-2958.2005.tb00864.x
|View full text |Cite
|
Sign up to set email alerts
|

A Multimethod Multitrait Validity Assessment of Self-Construal in Japan, Korea, and the United States

Abstract: A large number of previous studies have used self-construal to predict communication outcomes. Recent evidence, however, suggests that validity problems may exist in self-construal measurement. The current study conducted a multimethod multitrait (Campbell & Fiske, 1959) validation study of self-construal measures with data (total N = 578) collected in Korea (N = 200), Japan (N = 212), and the U.S. (N = 166). The data showed that the Singelis (1994) Self-Construal Scale, the Cross, Bacon, and Morris (2000) R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 52 publications
2
32
0
Order By: Relevance
“…That is, defining the self by pure 'independent' psychological attributes on the TST, making individual attributions of social life, endorsing autonomous scenario choices, and explicitly endorsing definitions of an independent concept of self are orthogonal aspects of these cultures. These null results replicate the findings of Bresnahan et al (2005) and Grace and Cramer (2003) and underline the need for a more domain-and relationspecific locus of analysis. However, independence-interdependence theory predicts that each of these aspects of independence will be associated with self-enhancement, so we tested for those associations.…”
Section: Within Culture Effectssupporting
confidence: 87%
“…That is, defining the self by pure 'independent' psychological attributes on the TST, making individual attributions of social life, endorsing autonomous scenario choices, and explicitly endorsing definitions of an independent concept of self are orthogonal aspects of these cultures. These null results replicate the findings of Bresnahan et al (2005) and Grace and Cramer (2003) and underline the need for a more domain-and relationspecific locus of analysis. However, independence-interdependence theory predicts that each of these aspects of independence will be associated with self-enhancement, so we tested for those associations.…”
Section: Within Culture Effectssupporting
confidence: 87%
“…It has enjoyed unmatched popularity and admiration; yet, the numbers that we so readily use to explain all sorts of cross-cultural phenomena may not adequately represent the underlying theoretical construct IND-COL and may be not much more than just quantitative noise (c.f. Bresnahan et al, 2005;Levine et al, 2003).…”
Section: Integrative Overview Of the Findingsmentioning
confidence: 99%
“…According to meta-analytic reviews by Oyserman et al (2002) and Taras et al (2010), the number of empirical studies that use unidimensional measures of IND-COL (instruments that yield a single IND-COL score) is roughly equal to that of studies that rely on instruments measuring IND-COL as two independent constructs (and yield two separate scores for IND and COL). Further complicating the matter, some of the studies that measured IND and COL separately found near-zero correlations (e.g., Singelis, 1994), negative correlations (e.g., Lam, Chen, & Schaubroeck, 2002), or even positive correlations (e.g., Bresnahan et al, 2005) between IND and COL.…”
mentioning
confidence: 99%
“…Theoreticians other than Kağıtçıbaşı suggest that the self should be addressed on three different aspects (Bresnahan, Chiu & Levine 2004, Bresnahan et al, 2005, Brewer & Gardner, 1996Hardie, Kashima & Pridmore, 2005;Kashima & Hardie, 2000, Schott & Bellin, 2001Uleman et al, 2000). The triple self-models include a third aspect that is called as relational self, familialism or personal collectivism in addition to the existing aspects of individualism and collectivism.…”
Section: Introductionmentioning
confidence: 99%